2019
DOI: 10.3390/f10040324
|View full text |Cite
|
Sign up to set email alerts
|

Timing is Not Everything: Assessing the Efficacy of Pre- Versus Post-Harvest Herbicide Applications in Mitigating the Burgeoning Birch Phenomenon in Regenerating Hardwood Stands

Abstract: Sweet birch (Betula lenta L.) is aggressively recruiting in temperate forest understories of the eastern United States and often dominates the post-disturbance seedling community, diminishing diversity and hindering sustainable silviculture. The type and timing of silvicultural actions affect birch recruitment via their effects on seedling recruitment, survival, and growth. Here, we examine birch regeneration under two contrasting treatment sequences: pre- versus post-shelterwood harvest herbicide application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Within the first 4 years of mitigating the deeply shaded conditions caused by fern, we significantly increased seedling density by nearly two‐fold and altered the advance regeneration layer composition to include several shade‐intolerant or intermediately tolerant species. Nonetheless, these species remain shaded beneath an intact canopy, thus overstory removal treatments timed with herbicide treatments or mechanical removal to control the fern layer will likely be required to capitalize on the diversity gains made by controlling the recalcitrant fern layer (Ristau et al, 2011; Royo et al, 2019). Moreover, despite not detecting strong deer browsing impacts on the small seedlings censused in this study during an era of lower deer densities (i.e., <8 deer·km −2 ), a wealth of evidence demonstrated that diverse regeneration often hinges on managing deer impacts when densities are higher (Côté et al, 2004; Horsley et al, 2003; Nuttle et al, 2013; Russell et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Within the first 4 years of mitigating the deeply shaded conditions caused by fern, we significantly increased seedling density by nearly two‐fold and altered the advance regeneration layer composition to include several shade‐intolerant or intermediately tolerant species. Nonetheless, these species remain shaded beneath an intact canopy, thus overstory removal treatments timed with herbicide treatments or mechanical removal to control the fern layer will likely be required to capitalize on the diversity gains made by controlling the recalcitrant fern layer (Ristau et al, 2011; Royo et al, 2019). Moreover, despite not detecting strong deer browsing impacts on the small seedlings censused in this study during an era of lower deer densities (i.e., <8 deer·km −2 ), a wealth of evidence demonstrated that diverse regeneration often hinges on managing deer impacts when densities are higher (Côté et al, 2004; Horsley et al, 2003; Nuttle et al, 2013; Russell et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the large seedling and sapling B. lenta and Carya that we documented, which are species mid‐tolerant of shade, are either less abundant or absent from comparable unmanaged second‐growth L. tulipifera forests (Clebsch & Busing 1989; Lafon 2004). Establishment and recruitment of B. lenta responds positively to canopy disturbance, with studies showing that once established, B. lenta can survive long periods of suppression (Yanai et al 1998; Royo et al 2019). Similarly, the limited amount of data available specific to Carya suggests seedling and sapling‐sized Carya positively respond to thinning and can persist in the understory >40 years (Lefland et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon poses a challenge to managers in sustaining forest diversity and values, as future forests are at risk of becoming increasingly monodominant. Royo et al [12] examined birch regeneration under contrasting treatment sequences consisting of either pre-or post-harvest herbicide application in a shelterwood system applied to hardwood-dominated stands of northern Pennsylvania, USA. The authors also used fences to investigate the potential interactions between the timing of herbicide application (pre-or post-harvest) and white-tailed deer (Odocoileus virginianus Zimmerman) browsing.…”
Section: Summary Of Papers Included In the Special Issuementioning
confidence: 99%